Characteristics of Response of Piezoelectric Actuators in Electron Flux Excitation - Philip C. Hadinata; John A. Main (Institute for Research and Community Services, Institut Teknologi Bandung, 2003)
In this paper the working parameters of non-contact strain control for piezoelectric ceramics are evaluated. The piezoelectric material functions as an actuator that transforms electrical into mechanical energy, and the electrical input is carried out by electron flux on the positive surface. The sample is exposed to some quasi-static inputs, and its responses are recorded using strain gages. The data shows faster and more stable response in the positive regime, but significantly slower response with drift in the negative regime. An electron collector is introduced on the positive surface to enhance the response in the negative regime. Theoretical analyses of energy transfer and electron movements is discussed, and a string of working conditions for controlling the surface strain of piezoelectric material are given as conclusions.